Features of structure formation when surfacing steel (iron) on titanium with plasma sprayed coatings in the technology of obtaining butt joint of bimetallic plates "titanium – steel" - Korzhyk, Volodymyr; Khaskin, Vladyslav; Ganushchak, Oleg; Strohonov, Dmytro; Illiashenko, Yevhenii; Fialko, Nataliia; Guo, Chunfu; Grynyuk, Andrii; Peleshenko, Sviatoslav; Aloshyn, Andrii (Eastern-European Journal of Enterprise Technologies, 2023)
The object of this study is structural formation during the surfacing of steel (iron) on titanium with plasma-sprayed coatings to obtain a butt connection of titanium-steel bimetallic plates. The task to be solved was to devise a technology for applying a barrier layer between titanium and steel to obtain a defect-free butt joint of the edges of bimetallic sheets of carbon steel, clad with a layer of titanium, under conditions of arc or plasma surfacing of carbon steel on titanium. The application of the barrier layer was carried out by plasma spraying of steel wire or iron powder. In this case, a coating with a thickness of 150...750 μm was applied on Grade2 titanium, on which 1–2 mm thick layers of materials similar to the sprayed ones were deposited by arc and plasma deposition. It was established that during spraying with subsequent surfacing of steel wire or iron powder, the main technological factors for eliminating cracks in the resulting compound are the thickness of the sprayed coating and the amount of linear surfacing energy. The thickness of the sprayed coating was selected (at least 400...600 microns) followed by plasma surfacing of ER70S-6 steel wire with a diameter of 1.0 mm or CNPC-Fe200 iron powder with unit energy up to ~200...250 J/mm. A defect-free transition layer from titanium to steel was obtained. It is a continuous layer with a thickness of 50–60 microns, consisting of intermetalides FeTi and FeTi2, as well as a β-phase titanium with an enhanced iron content, which retains certain ductility without cracks and other defects. With the help of the devised approach for connecting titanium-steel bimetallic edges, it is planned to manufacture seam bimetallic pipes for main pipelines to transport oil and gas raw materials extracted from wells.